Social Conflict in the Linguistic Landscape of Teen Language in the Digital Era - Mokodompit, Isnawita; Basalama, Nonny; Miolo, Sartin; Muziatun, Muziatun (RIRAI Publisher, 2025)
This study investigates social conflicts associated with teen language use on social media and messaging applications such as WhatsApp, TikTok, and Instagram, as well as within the communication focus of schools and learning surroundings. The main research issue revolves around the tensions caused by the use of informal youth language, including slang, abbreviations, emojis, code switching, and the tensions from adults expecting a more formal communicative structure. This research employs an ethnographic approach, specifically the youth language analysis via metadata and corpus-based techniques. This study incorporated observations as well as focused and conflict-centered, specifically student-teacher, deep interviews. The principal findings state that the use of informal language and the clash of its use within the expectations of the school and learning habitat is a major source of conflict, thus contributing to the overall